Electric Transmission Tower Corrosion Assessment Using Analytic Hierarchy Process and Health Index - Izhar A.S.M.; Khalid N.H.N.; Usman F.; Bakar M.S.A.; Adriyanshah N.F.; Zahari H. (Universiti Putra Malaysia Press, 2025)
A transmission tower is one of the components in power infrastructure supporting overhead power lines (OHL). Electrical components, structural, and environmental factors are classified as the primary concern as they can cause catastrophic failure in transmission lines. Transmission towers are in various environments, such as coastal and industrial areas, with different atmospheric corrosion levels due to various corrosive pollutants. For maintenance planning, it is essential to consider the effects of corrosion on towers by physical evaluation influenced by atmospheric corrosion. The physical evaluation of each element uses a scoring or rating method ranging from one to five. The Analytic Hierarchy Process (AHP) and Health Index (HI) are used to evaluate the overall condition of the towers. The study discovered that soil corrosivity in coastal areas is high, and atmospheric corrosion is due to chloride content. Although the pollutants in those areas are high and corrosive, the physical evaluation found that most industrial, coastal, and road towers are in good condition at a rating of 4 and 5. The HI result is the dominance of 71% to 85%, which indicates that the towers are in good health. ? Universiti Putra Malaysia Press.